The Childhood Maltreatment Modulates the Impact of Negative Emotional Stimuli on Conflict Resolution - Meng, Xianxin; Gao, Shuling; Liu, Wenwen; Zhang, Ling; Suo, Tao; Li, Hong (Frontiers in Psychology, 2019)
It has been reported that negative emotional stimuli could facilitate conflict resolution. However, it remains unclear about whether and how the impact of negative emotional stimuli on conflict resolution varies depending on childhood maltreatment. To clarify this issue, seventy-nine subjects were required to perform an arrow Eriksen Flanker Task which was presented in the center of emotional pictures. The present study found a significant interaction effect of childhood maltreatment and emotion on executive attention scores in reaction times (RTs) that reflect conflict resolution speed. For subjects in high childhood maltreatment, negative pictures elicited smaller executive attention scores in RTs than neutral and positive pictures, while neutral and positive pictures elicited similar executive attention scores in RTs. By contrast, for subjects in low childhood maltreatment, executive attention scores in RTs were similar across three conditions. These results suggest that the speed of conflict resolution is enhanced in high, instead of low, childhood maltreatment in situations of negative stimuli. This finding extends our understanding of the interaction among emotion, childhood maltreatment and conflict resolution.